PEMERIKSAAN GULA DARAH DAN PENDIDIKAN KESEHATAN TENTANG DIABETES MELITUS DI DESA KALIJAGA KABUPATEN LOMBOK TIMUR TAHUN AJARAN 2021/2022 GENAP - Maruli Taufandas (Jurnal Pengabdian kepada Masyarakat Cahaya Mandalika (Abdimandalika), 2022)
The purpose of this science and technology-based community service activity (PBI) aims to provide insight into knowledge and understanding of the community in Kalijaga Village, East Lombok Regency about diabetes mellitus. The target of science and technology-based community service (PBI) is the elderly in Kalijaga Village, East Lombok Regency. Dissemination of information about Diabetes Mellitus, especially in terms of preventing the occurrence of diabetes mellitus, is rarely done in the community. The problem is solved by three stages of activities, namely: preparation, implementation, and evaluation. The preparation stage starts from the preparation of proposals, coordination with partners, preparation of tools and materials, and publication of invitations. The implementation is done by checking blood sugar, and health education about diabetes mellitus diet, using lecture method (presentation technique), discussion, and question and answer. The evaluation was carried out with a pre-post test of health education activities and conducting a survey of 70% of the total targets to determine the success of community service activities. The results of community service activities show the level of success with an indication of a match between blood sugar checks, health education about diabetes mellitus and the needs of the elderly in Kalijaga Village, East Lombok Regency.